TYPOLOGY OF ROCK ART AT THE WAKUNTAI CAVE SITE IN MUNA REGENCY, SOUTHEAST SULAWESI - Muh. Aprisal Oka; Hasdairta Laniampe; Asma Sari (SANGIA: Jurnal Penelitian Arkeologi, 2024)
Wakuntai Cave site is a site that has rock arts. This research was conducted in Liang Kabori Village, Lohia District, Muna Regency with the aim of knowing the typology of rock arts in Wakuntai Cave. The methods used include primary data collection through field observations and map making using ArcMap 10.8 software, as well as classification methods. The collected data were then classified or grouped based on the attributes contained in the rock arts. This research managed to find 112 rock arts from 23 panels. The classification results show that there are four rock art motifs, namely human, animal, geometric and abstract motifs, which are then identified into 12 typologies.